Ricky Ricotta's mighty robot : the first adventure novel - Pilkey, Dav, 1966- (Scholastic, 2000)
Ricky Ricotta, a small mouse, saves a giant robot from his evil creator, Dr. Stinky, and in turn, the robot protects Ricky from the bullies at school and it saves the city from Dr. Stinky's plan to destroy it.